The effect of digital count-down display on signalized junction performance - Ibrahim, M.R.; Karim, M.R.; Kidwai, F.A. (2008)
Intersections are bottleneck in the highway networks and critical determinant of system's capacity and safety. Recently, several countdown timers had been installed at intersections in Kuala Lumpur and some other cities in Malaysia. The function of these timers is to aid drivers to judge the amount of time left for them to get the green signal for moving (starting) their vehicles as well as the amount of green time available for them to proceed across the intersection or to stop safely before the signal turns red. This advance information is supposed to help drivers in reducing their initial delay, especially for the first few vehicles and improving safety level. In the present research six intersections, three with count down timers and three with no-count down timer are analyzed to study the effect of count down timer on driver behavior, intersection approach headway and safety levels. The study suggests that countdown timer has got little effect on initial delay but the effect on headway is significant. The violation of traffic light by the drivers for countdown and normal signal is also compared.